The Effect of Financial and Non-Financial Variables to Firm Performance: Comparison Between Indonesia and Thailand - Hasni Yusrianti; Tien Norma Habsari; Suthawan Prukumpai (Universitas Muhammadiyah Yogyakarta, Indonesia, 2016)
The purpose of this research is to test the effect of financial and non-financial variables to firm performances between Indonesia and Thailand. The observation data used in this study is manufacturing companies from several sectors. Secondary data was used, collected from Indonesia Stock Exchange and Stock Exchange of Thailand during 2011 - 2013. By combining 3 years research, there are 55 Indonesian companies and 50 Thailand companies that meet predetermined criteria. Multiple Regression was used to analyze. This study uses Return on Equity, Earnings per Share, Market Value Added as financial variables and Earnings Quality, Institutional Ownership, Independent Commissioner, Audit Committee, Corporate Social Responsibility as non-financial variables. Test results show that both financial and non-financial variables can effect to firm performance.